2016
DOI: 10.1161/jaha.116.003370
|View full text |Cite
|
Sign up to set email alerts
|

Smoker's Paradox in Patients With ST‐Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: BackgroundPrior studies have found that smokers undergoing thrombolytic therapy for ST‐segment elevation myocardial infarction have lower in‐hospital mortality than nonsmokers, a phenomenon called the “smoker's paradox.” Evidence, however, has been conflicting regarding whether this paradoxical association persists in the era of primary percutaneous coronary intervention.Methods and ResultsWe used the 2003–2012 National Inpatient Sample databases to identify all patients aged ≥18 years who underwent primary pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 41 publications
6
58
0
5
Order By: Relevance
“…Of note, our findings of decreased likelihood of mortality associated with obesity and smoking are consistent with some other studies of the “obesity paradox” 15 and “smoker’s paradox” 16 , felt to represent asymmetry of baseline risk factors rather than protective effect. This paradox has been observed in other studies of STEMI in the NIS 17 . Our finding that weekend admission was associated with increased rates of respiratory failure may be related to the fact that multiple studies and a systematic review have suggested that STEMI patients admitted during weekends and off-hours have worse outcomes related in part to delays in presentation and longer door-to-reperfusion times 18 .…”
Section: Discussionsupporting
confidence: 57%
“…Of note, our findings of decreased likelihood of mortality associated with obesity and smoking are consistent with some other studies of the “obesity paradox” 15 and “smoker’s paradox” 16 , felt to represent asymmetry of baseline risk factors rather than protective effect. This paradox has been observed in other studies of STEMI in the NIS 17 . Our finding that weekend admission was associated with increased rates of respiratory failure may be related to the fact that multiple studies and a systematic review have suggested that STEMI patients admitted during weekends and off-hours have worse outcomes related in part to delays in presentation and longer door-to-reperfusion times 18 .…”
Section: Discussionsupporting
confidence: 57%
“…This effect was even more pronounced in high‐risk patients, especially those with ACS; this has been defined as “the smoking paradox.” The reasons for this paradoxical effect of smoking are not completely known, but could be related to an induction of CYP1A2 by cigarette smoking, which would lead to an increased production of the active metabolite of clopidogrel . However, the interaction of smoking in patients with ACS remains controversial, with recent studies having questioned the role of smoking as a positive prognostic factor in ACS patients, while others have shown that smokers on clopidogrel have a better outcome than non smokers on clopidogrel …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested better short-term outcomes among smokers with myocardial infarction (MI), a phenomenon known as the "smoker's paradox." [2][3][4][5][6] This may be because of the lower age and baseline risk profile in smokers compared with nonsmokers. However, recent studies have highlighted the detrimental influence of smoking on short-and longterm outcome in ACS patients, with a substantially higher risk for re-infarction, stent thrombosis, and death in smokers, irrespective of age.…”
mentioning
confidence: 99%